RISE: Achieving business sustainability through green innovation / Dr Zuhairah Hasan, Siti Norashikin Bashirun and Muna Kameelah Sauid - Hasan, Zuhairah; Bashirun, Siti Norashikin; Sauid, Muna Kameelah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
The term "sustainable development" began to gain wide acceptance in the late 1980s. According to Organisation for Economic Co-operation and Development (OECD), the economic growth alone was acknowledged as insufficient to solve the world's problems; the economic, social and environmental aspects of any action are essentially interrelated. The growing concern for the depletion of natural resources and environmental degradation around the globe, has significantly increased the pressure on businesses to achieve sustainable development. Thus, why is sustainability in business important? Businesses cannot operate independently of nature because they require resources to produce necessary materials and services (Ullah, Khan, & Ahmad, 2022). Hence, sustainable development is an increasingly popular approach aiming at achieving long-term global well-being, by sound economic and natural resource management, as well as through respect for people and other living things (Blackburn, 2007).